Mitotherapy for Fatty Liver by Intravenous Administration of Exogenous Mitochondria in Male Mice - Fu, Ailing; Shi, Xianxun; Zhang, Huajing; Fu, Bin (Frontiers in Pharmacology, 2017)
Mitochondrial dysfunction is a major and common mechanism in developing nonalcoholic fatty liver disease (NAFLD). Replacement of dysfunctional mitochondria by functional exogenous mitochondria may attenuate intrahepatic excessive lipid and recover hepatocyte function. However, no data shows that mitochondria can be systemically administrated to animals to date. Here we suggest that mitochondria isolated from hepatoma cells are used as a mitotherapy agent to treat mouse fatty liver induced by high-fat diets. When the mitochondria were intravenously injected into the mice, serum aminotransferase activity and cholesterol level decreased in a dose-dependent manner. Also, the mitotherapy reduced lipid accumulation and oxidation injury of the fatty liver mice, improved energy production, and consequently restored hepatocyte function. The mitotherapy strategy offers a new potential therapeutic approach for treating NAFLD.